Percepção de educadores e pais sobre as etapas de 24 a 36 meses do livro Ages and Stages Questionnaires-3 Actividades de Aprendizaje - Oliveira, Dáffini Henrique (Universidade Federal de São Carlos, 2020)
Due to the possibilities of use in the field of early childhood education, the instrument for screening and monitoring child development Ages and Stages Questionnaires Brasil (ASQ-BR) has gained space and visibility in the Brazilian scenario, after its translation and cross-cultural adaptation in 2010. Consisting of 19 questionnaires, intended for children 5 to 66 months of age, ASQ-BR has good psychometric properties. From this instrument, the book the ASQ-3Actividades de Aprendizaje was developed in 2013 and published in 2016 with the intention of being a joint resource to ASQ-3, providing parents and educators, from an easily understood language, with game ideas educational and interactional, which enable the enrichment of children's development. The book covers ages between 0 and 60 months and is divided into five development domains: Communication, Large Motor, Fine Motor, Problem Solving and Personal-Social, according to the ASQ-3 intervals. Since the use of the material is unprecedented in Brazil, this study aimed to understand the perceptions of educators and parents about a part of the book ASQ-3Actividades de Aprendizaje, corresponding to 24 to 36 months of age, as a resource to promote child development . This is a descriptive, exploratory and cross-sectional study with a qualitative approach. Seven educators and nineteen parents linked to the Municipal Centers for Early Childhood Education of a municipality in the interior of São Paulo participated in this study. The results demonstrate that the translation and adaptation process enabled a detailed analysis of the content described in the book fragment, the correction of divergence between the existing proposals in the preparation of the material, in which the final material obtained the consensus of the evaluators, being then sent and approved by the authors and publisher at the end of the process. Regarding the understanding of Child Development (DI), all educators and parents consider it relevant to monitor DI, the educators focusing on the importance of continuing education as a space that fosters reflection on educational practice and parents, based on perspective on typical and atypical development, as well as development milestones. As for the material of the ASQ-3 Learning Activities (Portuguese-BR) in the stages of 24 to 36 months, it proved to be clear, with objectivity of language and relevance in the educational and family contexts. It was also found that the activities of the book ASQ-3 Learning Activities (Portuguese-BR) in the stages of 24 to 36 months can be used in conjunction with the ASQ-3 instrument, supporting the application of the questionnaire, reinforcing that life activities daily activities can be considered spaces that promote Child Development (DI) and monitoring.
Perception of educators and parents on the steps of 24 to 36 months of the book Age and Questionnaire Stage-3 Learning Activities
Keywords: Desenvolvimento infantil; Educação infantil; Monitoramento; Vigilância do desenvolvimento; Família; Ages and Stages Questionnaires Brasil (ASQ-BR); ASQ-3 Actividades de Aprendizaje; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL